2021
DOI: 10.1101/2021.08.30.458264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated drift of receptive fields during noisy representation learning

Abstract: Long-term memories and learned behavior are conventionally associated with stable neuronal representations. However, recent experiments showed that neural population codes in many brain areas continuously change even when animals have fully learned and stably perform their tasks. This representational "drift" naturally leads to questions about its causes, dynamics, and functions. Here, we explore the hypothesis that neural representations optimize a representational objective with a degenerate solution space, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
1
13
1
Order By: Relevance
“…Representational drift has also been studied at the computational/theoretical levels [26][27][28][29]. In particular, Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Representational drift has also been studied at the computational/theoretical levels [26][27][28][29]. In particular, Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Other computational modeling work has also proposed that RD may arise due to plasticity-driven perturbations [44][45][46] . In 44 the authors studied a network with prescribed synaptic weights which allow for the storage of a large number of sequential patterns.…”
Section: Discussionmentioning
confidence: 99%
“…While the observed slow drift in neural and behavioral space in expert animals suggests that the changes in neural circuits occur in directions of neural state space that affect motor output, it remains to be seen whether this behavioral drift constitutes a learning process that optimizes a utility function such as energy expenditure (Srinivasan & Ruina, 2006) or magnitude of the control signal (Todorov & Jordan, 2002). Alternatively, it could reflect a random walk in a degenerate motor space that preserves task performance (Chaisanguanthum et al, 2014; Qin et al, 2021). Previous work has also suggested that motor variability could be explicitly modulated to balance exploration and exploitation as a function of past performance and task uncertainty (Dhawale et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Two main theories have been put forth to explain the apparent paradox of stable memories in plastic circuits. In the commonly held view that motor control is governed by low-dimensional dynamics (Gallego et al, 2017; Jensen et al, 2021; Shenoy et al, 2013; Vyas et al, 2020), the paradox can be resolved by having a degenerate subspace in which neural activity can change without affecting behavior (Rokni et al, 2007) or task performance (Qin et al, 2021). While this would do away with the requirement for stable activity at the level of single neurons (Figure 1A) (Clopath et al, 2017), it requires any drift in population activity to occur exclusively in the degenerate subspace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation